2019
DOI: 10.1016/j.mycmed.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in a Portuguese tertiary care hospital: Analysis of a 2-year period

Abstract: Background: Candidemia is a nosocomial infection of increasing importance, associated with high morbidity and mortality. The aim of this study is to describe the species distribution, risk factors, management and outcomes of patients with candidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
(22 reference statements)
2
17
5
Order By: Relevance
“…In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C. albicans was the most common cause of candidaemia in the whole hospital, but the proportion of non-C. albicans infections was higher than that of C. albicans infections. Moreover, the proportions of C. glabrata in surgical, internal medicine and paediatric wards were the highest, which is different from other studies in China [18,19,[35][36][37] but similar to other studies in other countries [4,22,27,29,32]. This may be due to the large number of elderly patients and the increasing use of azole antifungal agents.…”
Section: Discussioncontrasting
confidence: 87%
“…In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C. albicans was the most common cause of candidaemia in the whole hospital, but the proportion of non-C. albicans infections was higher than that of C. albicans infections. Moreover, the proportions of C. glabrata in surgical, internal medicine and paediatric wards were the highest, which is different from other studies in China [18,19,[35][36][37] but similar to other studies in other countries [4,22,27,29,32]. This may be due to the large number of elderly patients and the increasing use of azole antifungal agents.…”
Section: Discussioncontrasting
confidence: 87%
“…A recent study from Taiwan reported a significant association with survival outcome as well 37 . However, other previous studies have not found a significant difference, 38‐40 despite survivors having higher Equal Candida Scores than non‐survivors. The patient number was smaller in these studies.…”
Section: Discussionmentioning
confidence: 87%
“…The correlation between quality indicator scores and mortality has not been uniformly demonstrated. Huang and colleagues 11 showed a correlation between higher scores and survival while a study from Portugal failed to show any such association 21 . However, quality improvement may not always lead to a reduction in mortality, although that would be the most desirable benefit.…”
Section: Discussionmentioning
confidence: 99%